2012
DOI: 10.1103/physreva.85.042702
|View full text |Cite
|
Sign up to set email alerts
|

Role of the direct mechanism in dissociative recombination of HCO+and HOC+

Abstract: Studies of the direct mechanism for dissociative recombination of HCO + and HOC + are presented. The calculations involve wave-packet propagation in three dimensions on electronically resonant states of HCO and HOC with the potential-energy surfaces and autoionization widths obtained from ab initio electron scattering and electronic structure calculations. The total cross section and branching ratios for the two molecules and their deuterated isotopologues are calculated and compared to available experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
(66 reference statements)
3
19
0
Order By: Relevance
“…Recently, however, Fonseca dos Santos et al (2014) presented calculated DR coefficients as a function of temperature from $1 K to 5000 K for HCO + that were significantly larger than previous calculations had shown. There is less difference between the theoretical and the experimental values for the temperature dependencies of the cross sections and rate coefficients (e.g., Talbi et al, 1989;Kraemer and Hazi, 1989;Tomashevsky et al, 1998;Larson et al, 2005;Mikhailov et al, 2006;Douguet et al, 2008Douguet et al, , 2009Nordhorn et al, 2011;Pratt and Jungen, 2011;Larson et al, 2012).…”
Section: Rate Coefficients For Specific Dissociative Recombination Rementioning
confidence: 96%
See 2 more Smart Citations
“…Recently, however, Fonseca dos Santos et al (2014) presented calculated DR coefficients as a function of temperature from $1 K to 5000 K for HCO + that were significantly larger than previous calculations had shown. There is less difference between the theoretical and the experimental values for the temperature dependencies of the cross sections and rate coefficients (e.g., Talbi et al, 1989;Kraemer and Hazi, 1989;Tomashevsky et al, 1998;Larson et al, 2005;Mikhailov et al, 2006;Douguet et al, 2008Douguet et al, , 2009Nordhorn et al, 2011;Pratt and Jungen, 2011;Larson et al, 2012).…”
Section: Rate Coefficients For Specific Dissociative Recombination Rementioning
confidence: 96%
“…It appears then that reaction (RC1a) is the only significant channel in the DR of HCO + at temperatures relevant to planetary atmospheres. The calculations of Larson et al (2012) showed that up to energies of $0.5 eV, the indirect mechanism dominates the DR process, and the cross section falls off rapidly. At higher energies, the temperature dependence of the DR reaction is not as steep, and the branching ratio for channel (RC1c) becomes more important.…”
Section: Rate Coefficients For Specific Dissociative Recombination Rementioning
confidence: 98%
See 1 more Smart Citation
“…This is important because one possible explanation for the discrepancy between the simple model and the experiments for HCO + is that both the indirect and direct mechanisms contribute to the cross sections. However, the studies reported to date indicate that the direct mechanism should not be important at low energy because the calculated potential energy surfaces for the ground state ion and dissociative states of the neutral do not show any crossings near the equilibrium geometry of the ion [13][14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%
“…For molecules, new work includes: H + 2 including proton-production and dissociative ionisation (Zammit et al 2013), H 2 including excitation and dissociation (Lan & Leon 2012, Wang et al 2013a, Ki & Jung 2013, excitation of HD + (Motapon et al 2014), dissociative ionisation of D 2 (Lower et al 2013), dissociative recombination of LiH + 2 (Thomas et al 2014), excitation of BeH + (Chakrabarti & Tennyson 2012, Niyonzima et al 2013, elastic, inelastic and total cross sections for HCN (Sanz et al 2012), elastic and inelastic scattering on H 2 CN ), dissociative recombination of N + 2 , excitation and dissociation of N 2 (Malone et al 2012, Laporta et al 2014, Xin & Ding 2014, excitation of H 2 O (Rescigno & Orel 2013), dissociative ionisation of HDO + (Defrance et al 2014), elastic and inelastic scattering on CO (Laporta et al 2012, Ristić et al 2012, Wang et al 2013b (Larson et al 2012), elastic and inelastic scattering on NO (Chiari et al 2013), total scattering and excitation cross sections for N 2 O (Vinodkumar & Barot 2012, Watanabe & Takahashi 2014, elastic, excitation and ionisation cross sections for NCO (Kaur & Baluga 2012), elastic, excitation and ionisation processes on O 2 (Singh & Baluja 2014), fragmentation of CO 2+ 2 , excitation of NF 3 (Goswami et al 2013), and elastic scattering on OCS and CS 2 (Murai et al 2013).…”
Section: Electron-molecule and Electron-molecular Ion Scatteringmentioning
confidence: 99%